Rational Doping Strategy to Build the First Solution‐Processed p‐n Homojunction Architecture toward Silicon Quantum Dot Photodetectors - Batu Ghosh; Hiroyuki Yamada; Kazuhiro Nemoto; Wipakorn Jevasuwan; Naoki Fukata; Hon‐Tao Sun; Naoto Shirahata (Small Science, 2024)
Semiconductor p‐n homojunction is a requisite building block of operating transistors and diodes which make up the modern electronic circuits and optoelectronic applications. However, it has been so far limited to bulk form of single crystals such as silicon (Si) or gallium arsenide. Herein, a brand‐new method of constructing p‐n homojunction architectures that breaks through the limitation is presented. Colloidal inks of p‐type and n‐type Si quantum dots (QDs) are synthesized by thermal disproportionation of (HSiO1.5)n doped with boron or phosphorus, followed by surface ligand engineering. Analysis combining UV photoelectron spectroscopy, electron spin resonance, and current–voltage characteristics confirms that an orthogonal solvent trick makes clean interfaces between n‐type and p‐type SiQD layers without disruption on film formation. The forward and reverse current–voltage characteristics of the diode, along with various spectroscopic characterizations, demonstrate the formation of the first p‐n homojunction of SiQDs. The self‐powered photodiode provides a tunable response specific to the wavelength.